2014
DOI: 10.1007/s10549-014-3201-6
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/mTOR dual inhibitor P7170 demonstrates potent activity against endocrine-sensitive and endocrine-resistant ER+ breast cancer

Abstract: Purpose Activation of the phosphatidylinositol 3-kinase (PI3K)/AKT/mTOR pathway has been implicated in anti-estrogen resistance in breast cancer. We tested the therapeutic potential of the novel PI3K/mTOR dual inhibitor P7170 in a panel of anti-estrogen-sensitive and -resistant models of ER+ breast cancer. Methods Estrogen receptor-positive (ER+) breast cancer cells were treated +/− P7170. Fresh cores from primary ER+/HER2− tumors from two patients were treated +/− P7170 ex vivo. Mice bearing breast cancer x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…While we previously found that smaller MCF-7 tumors regress in response to fulv (38), larger tumors (500–1,000 mm 3 ) are generally unresponsive (Fig. S10 and Table S2).…”
Section: Resultsmentioning
confidence: 73%
“…While we previously found that smaller MCF-7 tumors regress in response to fulv (38), larger tumors (500–1,000 mm 3 ) are generally unresponsive (Fig. S10 and Table S2).…”
Section: Resultsmentioning
confidence: 73%
“…This quinoline compounds demonstrated potent inhibition activity on mTORC1/mTORC2/ALK1, cell cycle arrest, induction of apoptosis, antiangiogenic activity. Moreover, it showed antitumor efficacy on both in vitro and in vivo studies against the erlotinib–sensitive and –insensitive models NSCLC and anti-estrogen models of ER+ breast cancer [ 86 , 87 , 88 ], reaching the clinical trials evaluation for patients with advanced refractory solid tumours ( number NCT01762410) [ 89 ].…”
Section: Quinolines As Inhibitors Of Carcinogenic Pathwaysmentioning
confidence: 99%
“…Breast tumor samples were obtained after patients provided written informed consent for research use and the research was approved by the Ethics Committee of our institution. We performed this experiment according to Dr Jennifer R. Bean's paper . Untreated primary tumor samples from four patients with early‐stage ER+/HER2‐breast cancer were collected by using core needle biopsy, later confirmed by pathological examination.…”
Section: Methodsmentioning
confidence: 99%
“…We performed this experiment according to Dr Jennifer R. Bean's paper. (3) Untreated primary tumor samples from four patients with early-stage ER+/HER2-breast cancer were collected by using core needle biopsy, later confirmed by pathological examination. Within 1 h post-biopsy, samples were put into DMEM medium (Corning, NY, USA) with 10% fetal bovine serum (FBS) after several brief washes with 1XPBS, 100 nM Fulvestrant and 30 nM AUY922 was added in the medium for each single group and kept for 48 and 24 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation